Location choice of German multinationals in the Czech Republic. The importance of agglomeration economies - Veronika Hecht (FIW - Research Centre International Economics, 2015)
This paper analyses the location choice of German investors in the Czech Republic based on a unique dataset covering all Czech companies with a German equity holder in 2010. The identification of the regional determinants of foreign direct investment (FDI) location is an important regional policy issue as FDI is supposed to improve the labour market conditions of the host region. Using a nested logit approach the impact of agglomeration economies, labour market conditions and distance on the location choice decision is investigated. The main result of the paper is that apart from a low distance to the location of the parent company the attractiveness of a Czech district for German investors is mainly driven by agglomeration economies. Besides localisation economies the agglomeration of German companies in a region plays a decisive role. The importance of labour market characteristics differs between investment sectors, sizes and periods.
Keywords: F24; R12; R30; 330; Location choice; FDI; Multinational enterprises; Germany; Czech Republic; Agglomeration Economies